2017
DOI: 10.1002/maco.201709818
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatment on the cavitation erosion resistance of stainless steel

Abstract: To evaluate the effect of heat treatment on the cavitation erosion resistance of stainless steel, an experimental investigation is carried out using a cavitating jet test apparatus complying with the ASTM G134 standard. The jet pressure is 30 MPa and the cavitation number is 0.014. Specimens made of stainless steel SUS630 are aged at different temperatures. Prior to cavitation erosion experiment, the mechanical properties of the specimens are obtained through an inverse analysis method in conjunction with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Studies conducted by Peng et al [ 78 ] which looked at SUS630 steel exposed to various heat treatments to change steel characteristics, verified the relationship between erosion rate and such material attributes. Many correlations and models have been discussed so far, in which numerous relevant variables have been considered by various investigators to predict the actual pattern of erosion due to sediment and cavitation as indicated in Eqs.…”
Section: Problems Associated With Hydropower Plantmentioning
confidence: 87%
See 1 more Smart Citation
“…Studies conducted by Peng et al [ 78 ] which looked at SUS630 steel exposed to various heat treatments to change steel characteristics, verified the relationship between erosion rate and such material attributes. Many correlations and models have been discussed so far, in which numerous relevant variables have been considered by various investigators to predict the actual pattern of erosion due to sediment and cavitation as indicated in Eqs.…”
Section: Problems Associated With Hydropower Plantmentioning
confidence: 87%
“…L is the fluid's density. Peng et al [ 78 ] tested martensitic SUS630 stainless steel for cavitation erosion problems. It was found that yield stress and elastic modulus increased with ageing annealing at 480 °C–620 °C and solution annealing at 1040 °C, improving cavitation erosion resistance.…”
Section: Problems Associated With Hydropower Plantmentioning
confidence: 99%
“…9 Furthermore, ASTM G32-17 (indirect method) gives that provision of testing the combined result for cavitation, corrosion, and silt erosion by just adding acid or base and silt particle to the test liquid. 62 However, the indirect method limitation is the additions of other mandatory test parameters, i.e. standoff distance (SOD) and immersion depth (IMD) of the specimen.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…Undoubted effect of hardness on CER contributed to searching for methods of increasing material hardness or surface hardness. The most popular is thermal or thermochemical treatment, especially nitriding [31], [49], [50], which increase hardness and also improves other mechanical properties. The other way for increasing surface hardness is deposition of hard coatings (e.g.…”
Section: Coatingsmentioning
confidence: 99%